Konsep Pendidikan Integral Dalam Surat Al-Alaq Ayat 1-5 - Miftahillah Miftahillah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2020)
Abstract This study aims to improve the language of early childhood in Islam. This type of research is a library research with a qualitative descriptive approach. The data collection technique uses documentation techniques, while the data analysis technique uses content analysis techniques. The results showed that early childhood language boosted through three components, namely: family, school and community environment. The family has the first and foremost role in acquiring children's first language, teachers in schools also help in accelerating children with play activities, while the community environment plays a role through playmates who contribute to children's language and also a conducive environment to shape children's language development. The implementation of accelerating the language of early childhood in Islam so that parents and teachers before learning with children, pray with children according to the advice of Allah SWT in the Qur'an surah Al Kahfi verses 25-28, surah Thaha verse 109 and the call to prayer has been introduced since babies and tauhid sentences from an early age. Keywords: Islam ; Language, Early Childhood